Advancing the Interdisciplinary Collaborative Health Team Model: Applying Democratic Professionalism, Implementation Science, and Therapeutic Alliance to Enact Social Justice Practice. (July 2015) - Murphy, Nancy
Abstract : This essay reframes the interdisciplinary collaborative health team model by proposing the application of 3 foundational pillars—democratic professionalism, implementation science, and therapeutic alliance to advance this practice. The aim was to address challenges to the model, enhance their functional capacity, and explicate and enact social justice practices to affect individual health outcomes while simultaneously addressing health inequities. The pillars are described and examples from the author's dissertation research illustrate how the pillars were used to bring about action. Related theories, models, and frameworks that have negotiation, capacity building, collaboration, and knowledge/task/power sharing as central concepts are presented under each of the pillars.